Implementation of Character Education through Accounting Learning in Shaping Student Attitudes and Behavior in Vocational High Schools - Rahmawati, Anggi Novita; Asmawan, Moh. Chairil (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The purpose of this study is to investigate the impact that character education plays in forming the perspectives and actions of students who are majoring in Accounting at SMK Negeri 6 Sukoharjo. The researcher used a method called purposive sampling to pick three participants, and then they conducted interviews with key informants who were involved in the formation and development of character education programs in schools. The data was gathered through many methods, including observation, interviews, and extra resources. Data was analyzed by thematic technique. The findings of the research indicate that SMK Negeri 6 Sukoharjo has successfully implemented character education in their school. The Inspirational Diary is a resource that students of Accounting use as a way to integrate character education into their curriculum. These findings are helpful for showing the significant role that character education plays within the setting of accounting education, and they provide vital insights that can be used to build school policies that are more efficient.